Analisis Motivasi Peserta Didik Terhadap Keterampilan Menyimak pada Mata Pelajaran IPAS di Kelas IV - Fadiyatul Iffah; Meliana Agustina; A. Syachruroji (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
This research was carried out on Tuesday, September 17 2024 at SDN Serang 04 with the aim of analyzing students' motivation towards listening skills in the science and sciences subject in class IV with material on plant body parts. This research uses a qualitative approach through descriptive methods. The data collection techniques used by researchers were observation, interviews and documentation. The number of students who were the objects of the researcher's research was 21 people. After researchers analyzed the motivation in students' listening skills, it turned out that the cause of this was students' lack of focus in listening and the use of less interactive learning media in class. Apart from that, the inhibiting factor is the role of the teacher in the learning process and the use of media, so that students are more passive in learning. The inhibiting factors for teachers in using learning media are the lack of school facilities and infrastructure, the lack of ability and creativity of teachers in using learning media so that the use of science and technology learning media has not been realized optimally. Therefore, researchers analyzed student motivation using learning media. The results of the research conducted by researchers can be concluded that the use of learning media can motivate students in their listening skills in the science and sciences subject in Class IV with material on plant body parts.